Bodies in the Novel Infinite Jest - Chapman, Ana; Chapman, Silvia; Cosentino, Stephanie (Frontiers in Psychology, 2021)
This manuscript provides a literary analysis of the use of bodies in David Foster Wallace’s novel Infinite Jest (1996). The novel describes a world where oversaturation of external stimulation leads to the perception of one’s own mind and body as prosthetic parts, malleable and deformed, wherein the mind fails to feel bodily sensations and characters experience a complete disconnectedness from the self and others. Indeed, characters’ disembodiment and sensations of disconnection lead them to a compulsive quest for connectedness through the use of masks, made-up feelings, mind-body hybrid pain, corporeal malleability and prostheses. These portrayals of the disordered and disconnectess between body and mind or self will be described and compared to clinical conditions characterized by a disconnection between mind and body and impaired body self-awareness. Through this exercise we argue that the use of scientifically inspired pathologized bodies are a means of conveying Wallace’s stance on or criticism of the degradation of society through excessive entertainment.